Micro-Electro Nanofibrous Dressings Based on PVDF-AgNPs as Wound Healing Materials to Promote Healing in Active Areas - Liu T; Xie F; Geng L; He R; Sun M; Ni T; Xu P; Xing C; Peng Y; Chen K; Fang Y (International Journal of Nanomedicine)
Tiantian Liu,1,2,* Feifei Xie,3,4,* Lele Geng,1,2 Ruizhe He,1,2 Mengzhe Sun,1,2 Tao Ni,1,2 Peng Xu,1,2 Chao Xing,1,2 Yinbo Peng,1,2 Ke Chen,3,4 Yong Fang1,2 1Department of Burns and Plastic Surgery, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Institute of Traumatic Medicine, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 3School of Materials Science and Engineering, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 4Shanghai Key Laboratory of Materials Laser Processing and Modification, Shanghai Jiao Tong University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yong Fang, Department of Burns and Plastic Surgery, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China, Email fangyong1020@hotmail.com Ke Chen, School of Materials Science and Engineering, Shanghai Jiao Tong University, Shanghai, People’s Republic of China, Email chenke83@sjtu.edu.cnPurpose: The purpose of this study is to develop an innovative solution for chronic wounds in high-mobility areas, such as joints, where conventional treatments are hindered by passive healing mechanisms and the need for immobilization. By designing a micro-electro-Nanofiber dressing composed of piezoelectric polyvinylidene fluoride (PVDF) integrated with antimicrobial silver nanoparticles (AgNPs), this research aims to address the dual challenges of promoting effective wound healing and maintaining joint mobility.Methods: Herein, we developed a novel micro-electro-Nanofiber dressing using electrospinning technology, incorporating polyvinylidene fluoride (PVDF) with silver nanoparticles (AgNPs). The optimized PVDF-AgNPs Nanofiber dressings exhibited strong piezoelectric effects suitable for joint wounds.Results: In vitro experiments demonstrated that the dressing effectively promoted fibroblast migration and collagen synthesis. In vivo, the dressing exhibited a trend of rapid healing in infected wounds within 12 days while modulating macrophage differentiation toward the anti-inflammatory M2 phenotype. Additionally, the incorporation of antimicrobial nanosilver effectively controlled local infections, further facilitating the healing process.Conclusion: To sum up, by harnessing the piezoelectric effect to stimulate endogenous healing mechanisms without restricting joint mobility, the developed PVDF-AgNPs Nanofiber dressings represent a transformative approach for the treatment of wounds in highly mobile body areas. Keywords: wound healing, piezoelectric materials, polyvinylidene fluoride, silver nanoparticles